2014
DOI: 10.1039/c4cp00578c
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in solid-state NMR spectroscopy of crystalline microporous materials

Abstract: This Perspective describes how solid-state NMR spectroscopy can be used to investigate the structure, disorder, dynamics and reactivity of crystalline microporous framework materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 124 publications
(359 reference statements)
0
92
0
Order By: Relevance
“…Wheatley and Morris observed that, in addition to expected disorder of the protonated and neutral N species of cyclam (owing to the presence of four N atoms and only two H + ), the entire SDA could be refined as occupying two orientations within the pores of AlPO-34(cyclam). 34 In order to investigate the presence of any non-periodic disorder of the SDA and potentially partially-occupied water species, all materials were characterised here by 1 H, 13 C, 15 N, 19 F, 27 Al and 31 P NMR spectroscopy with the experimental results compared to periodic DFT calculations to aid assignment and interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wheatley and Morris observed that, in addition to expected disorder of the protonated and neutral N species of cyclam (owing to the presence of four N atoms and only two H + ), the entire SDA could be refined as occupying two orientations within the pores of AlPO-34(cyclam). 34 In order to investigate the presence of any non-periodic disorder of the SDA and potentially partially-occupied water species, all materials were characterised here by 1 H, 13 C, 15 N, 19 F, 27 Al and 31 P NMR spectroscopy with the experimental results compared to periodic DFT calculations to aid assignment and interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as discussed in the Supporting Information (S7), it is difficult to distinguish between the two possible structures using the DFT-calculated 13 The low natural abundance (0.368%) and gyromagnetic ratio (15N/1H = 0.101) of larger chemical shift range (~900 ppm) compared to 13 C (~250 ppm) means that 15 N should be more sensitive to small differences in the local environment of the SDA, arising from, e.g., disorder. The 15 N CP MAS NMR spectra of the six forms of AlPO-34 are shown in Figure 2.…”
Section: Solid-state Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This is a suitable approach for studying ZIFs, owing to the variety of NMR-active nuclides present [17,18]. 1 H, 13 C and 15 N NMR spectroscopy can, in principle, be used to investigate the number, type and relative proportions of the framework linkers.…”
Section: Introductionmentioning
confidence: 99%
“…NMR spectroscopy has been widely used to investigate the structure of many solids, owing to its sensitivity to the local environment, without the need for any long-range order [15][16][17]. This is a suitable approach for studying ZIFs, owing to the variety of NMR-active nuclides present [17,18].…”
Section: Introductionmentioning
confidence: 99%